Analysis of Existing Constraints During Loading and Unloading of Goods at Belawan Port by PT. Gelora Perkasa - Sabila, Fadiyah Hani; Cahyadi, Wawan Dwi Yogo (Ebiz Prima Nusa, 2024)
The purpose of this paper is to discuss the analysis of constraints that exist during the loading and unloading of goods from ships to the dock and then until they are stored in the owner's warehouse. The research methods used in this study are field research and library research. The author found several constraints or obstacles in the loading and unloading process, namely constraints in the form of natural factors such as bad weather, strong winds, and rain. Under these conditions, unloading activities must be stopped to ensure the safety of goods and workers, as goods exposed to rain will be damaged and their quantity reduced, resulting in losses. In addition, the factor of damaged loading and unloading equipment also hampers the loading and unloading process, with equipment breakdown due to lack of maintenance from the mechanical division on the loading and unloading equipment and several other constraints. After identifying these constraints, PT. Gelora Perkasa has several efforts to minimize them, starting from constraints in the form of natural factors, where the action taken is to temporarily stop loading and unloading activities to prevent greater losses due to damage to goods. Meanwhile, to prevent the consequences of damaged loading and unloading equipment, it is necessary to carry out more intensive maintenance, and equipment that is no longer suitable for use should be replaced and no longer used to avoid obstacles during loading and unloading activities. Keywords: Loading and Unloading, Ports, Work Safety